Waterborne acrylic polyurethane antistatic coating and preparation method thereof

Through the combination of aqueous acrylic polyurethane resin and modified conductive barium sulfate powder, the color and construction problems of existing anti-static coatings are solved, efficient electrostatic protection and decorative requirements are achieved, and good hardness and resistance are provided.

CN119264747APending Publication Date: 2025-01-07SHANDONG NORTH MODERN CHEM IND
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411450918.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing anti-static coatings are dark in color and cannot meet the customers' decorative needs of light-colored surfaces. At the same time, the powder has a large proportion of weight, which is easy to precipitate during storage, and has poor construction properties. The wear and scratch resistance of the coating needs to be improved.

Method used

The conductive layer is prepared by in-situ chemical oxidation polymerization method by combining aqueous acrylic polyurethane resin with modified conductive barium sulfate powder, and a modified conductive barium sulfate powder with small specific gravity and high conductivity is used as a conductive filler, and uniform precipitation is combined with ammonia water. Method, design reasonable component compatibility to form a smooth and coherent conductive layer.

Benefits of technology

The color adjustment of the paint is realized, the decorative needs of light-colored surfaces are met, the specific gravity of the powder is reduced, the construction property and the hardness of the coating are improved, and the antistatic and electrical properties are good, and suitable for the coating of precision equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a water-based acrylic polyurethane antistatic coating and a preparation method thereof, and relates to the technical field of water-based coatings. The paint is prepared from a component A and a component B according to the mass ratio of (10-20): 1, the component A is prepared from deionized water, water-based acrylic resin, modified conductive barium sulfate powder, a functional additive and other raw materials; the component B is prepared from modified conductive polyurethane resin and propylene glycol diacetate; the modified conductive barium sulfate powder is obtained by coprecipitating barium sulfate powder through antimony salt and tin salt; the color of the waterborne acrylic polyurethane anti-static coating can be adjusted according to the needs of customers, and the decorative requirements of the customers on light-color surfaces are met; the raw material modified conductive barium sulfate powder has good compatibility with the modified conductive polyurethane resin, has good antistatic property, wear resistance and scratch resistance after being cured into a film, and has good mechanical properties; the coating powder has small specific gravity, is not easy to precipitate during storage, has good constructability, and is convenient to spray on precision equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water-based coatings, in particular to a water-based acrylic polyurethane antistatic coating and a preparation method thereof. Background Art

[0002] Static electricity is widely present in daily life and can be generated by contact or friction. It has the characteristics of low voltage and power, small current and short duration. It has little impact on conventional instruments and equipment, but for some sensitive instruments and equipment, static electricity voltage can cause greater harm. For example, when the static electricity accumulation on the surface of non-metallic parts such as polymer materials reaches a certain level, discharge will occur, causing various precision instruments and precision electronic components to break down and be damaged, and may even cause flammable and explosive materials to catch fire or explode, causing huge losses to life and property. In addition, the accumulated static electricity will seriously absorb dust, making cleaning more difficult. In order to prevent the generation and accumulation of static electricity, the commonly used method is to apply a layer of antistatic coating on the surface of the instrument.

[0003] Existing antistatic coatings can be mainly divided into carbon-based coatings, metal-based coatings, metal oxide-based coatings and coatings with added surfactants according to their different conductive components. However, the above coatings are dark in color and cannot meet customers' decorative needs for light-colored surfaces. In addition, in order to achieve a good antistatic effect, the powder has a large specific gravity, is easy to precipitate during storage, and has poor construction performance. Since the coating needs to be sprayed on precision equipment, the wear resistance and scratch resistance of the coating also need to be improved when the spraying thickness is very small. Summary of the invention

[0004] To solve the above problems, the purpose of the present invention is to provide a water-based acrylic polyurethane antistatic coating and a preparation method thereof.

[0005] In order to achieve the above object, the present invention is implemented through the following technical solutions: A water-based acrylic polyurethane antistatic coating, comprising component A and component B in a mass ratio of 10-20:1; component A comprises the following raw materials in parts by weight: 15-25 parts of deionized water, 30-45 parts of water-based acrylic resin, 20-30 parts of modified conductive barium sulfate powder, 3-5 parts of functional additives, 5-15 parts of pigments, 10-20 parts of fillers and 1-3 parts of ethylene glycol butyl ether; component B comprises the following raw materials: 5-9 parts of modified conductive polyurethane resin and 0.5-2 parts of propylene glycol diacetate; The modified conductive polyurethane resin is obtained according to the following steps: The iron salt and propylene glycol diacetate are mixed uniformly to obtain an iron salt solution with a mass concentration of 15-20%; Under stirring, the pyrrole monomer is added to the waterborne polyurethane resin several times, the temperature is raised to 40-50° C. and stirred for 10-20 minutes, an iron salt solution is added thereto, and stirring is continued for 1.5-2 hours to obtain a modified conductive polyurethane resin; The mass ratio of pyrrole monomer to waterborne polyurethane resin is 15-25:80; The molar ratio of iron salt to pyrrole in the iron salt solution is 1.8-2.2:1; The waterborne polyurethane resin has a solid content of 60-75% and an NCO content of 14-21%; The modified conductive barium sulfate powder is obtained by coprecipitating barium sulfate powder with antimony salt and tin salt.

[0006] Preferably, the modified conductive barium sulfate powder is prepared according to the following steps: Add antimony trichloride and tin dichloride dihydrate into dilute hydrochloric acid, heat to 58-62°C and stir for 2-3 hours to obtain a precursor solution; The barium sulfate powder is added to deionized water, ultrasonically dispersed uniformly, heated to 73-77°C and stirred for 1-2 hours, the precursor solution is added dropwise at a rate of 0.2-0.5 L / min, and after the addition is completed, the pH is adjusted to 1.0-2.0 with ammonia water, the temperature is raised to 88-92°C and stirred for reaction for 18-20 hours, filtered, washed with ethanol, dried, and calcined at 550-650°C for 2-3 hours to obtain modified conductive barium sulfate powder; The mass ratio of the antimony trichloride, tin dichloride dihydrate, dilute hydrochloric acid, barium sulfate powder and deionized water is 2-2.5:20-21:55-60:18-21:200.

[0007] Preferably, the functional additive is two or more of a wetting and dispersing agent, an aqueous defoaming agent, an aqueous pH regulator, an aqueous leveling agent, and an aqueous thixotropic agent.

[0008] Preferably, the pigment is one or more of anatase titanium dioxide, red iron oxide, medium chrome yellow, carbon black or phthalocyanine blue.

[0009] Preferably, the filler is two or more of heavy calcium, talc, kaolin or sericite powder.

[0010] Preferably, the solid content of the waterborne acrylic resin is 28-42%, and the hydroxyl content is 1.8-3.3%.

[0011] Preferably, the mass concentration of the dilute hydrochloric acid is 4-6 mol / L.

[0012] Preferably, the iron salt is ferric chloride or ferric nitrate.

[0013] The present invention also includes a method for preparing a water-based acrylic polyurethane antistatic coating, comprising the following steps: ① Grind 5-15 parts of pigment, 10-20 parts of filler, 15-25 parts of deionized water and 1-3 parts of ethylene glycol butyl ether to less than 40 μm by weight, add 30-45 parts of water-based acrylic resin, 20-30 parts of modified conductive barium sulfate powder and 3-5 parts of functional additives after filtering, and stir evenly to obtain component A; ② Mix 5-9 parts of modified conductive polyurethane resin and 0.5-2 parts of propylene glycol diacetate and stir evenly to obtain component B; When in use, component A and component B are stirred and mixed at a mass ratio of 10-20:1 to obtain a water-based acrylic polyurethane antistatic coating.

[0014] Preferably, in step ①, the stirring speed is 2800-4200 rpm, and the stirring time is 40-70 minutes.

[0015] Compared with the prior art, the present invention has the following advantages: The color of the waterborne acrylic polyurethane antistatic coating of the present invention can be adjusted according to the needs of customers, meeting the decorative needs of customers for light-colored surfaces. The waterborne acrylic polyurethane antistatic coating of the present invention, on the one hand, uses pyrrole and iron salt to modify the waterborne polyurethane resin. Specifically, the waterborne polyurethane is used as a matrix, polypyrrole is used as a conductive component, and an in-situ chemical oxidation polymerization method is used to compound the pyrrole monomer with the waterborne polyurethane to prepare a waterborne polyurethane / polypyrrole dispersion. A core-shell structure with a waterborne polyurethane resin as a core and polypyrrole as a shell. The π electrons on the double bonds in the polypyrrole molecule are similar to free electrons in metals. When current passes through, the π electrons on C=C move quickly along the polypyrrole molecular chain to form a conductive network. Polypyrrole is combined with the waterborne polyurethane resin in two ways: adsorption and embedding, forming a smooth, coherent polymer conductive layer.

[0016] On the other hand, modified conductive barium sulfate powder with low specific gravity and high conductivity is used as conductive filler. Antimony-doped tin dioxide is coated on the surface of barium sulfate powder by uniform precipitation method with ammonia water as precipitant. Conductive barium sulfate powder coated with pure tin dioxide crystals does not have conductive properties. The atomic radius of tin and antimony is similar. When the atomic radius difference between the two elements is less than 15%, these atoms can replace each other and form substitutional impurity defects. Antimony ions can partially replace the lattice of tin ions to form substitutional defects. The antimony ion impurities introduced by doping cause the SnO2 crystal to form crystal defects. This can provide conductive carriers for the material, giving the material semiconductor properties.

[0017] The modified conductive barium sulfate powder and modified conductive polyurethane resin components of the present invention are reasonably designed, the two components have good compatibility, and after curing into a film, they have good antistatic properties and good electrical properties; the coating has high hardness, good adhesion to the substrate, and good physical properties; the coating powder has a small specific gravity, is not easy to precipitate during storage, has good construction properties, and is convenient for the coating to be sprayed on precision equipment. It also has good salt water resistance, solvent resistance, moisture and heat resistance and other properties, and has a wide range of application scenarios. DETAILED DESCRIPTION

[0018] The purpose of the present invention is to provide a water-based acrylic polyurethane antistatic coating and a preparation method thereof, which is achieved by the following technical scheme: The water-based polyurethane resin is provided by Guangdong Huaguoshan Environmental Protection Technology Co., Ltd., model 400L.

[0019] The wetting and dispersing agent is a conventional wetting and dispersing agent, such as afcona 4560, BYK-191, Tech-8045; The water-based defoamer is a conventional water-based defoamer, such as afcona 2503, afcona2502, Tech-321W; The aqueous pH regulator is a conventional pH regulator, such as Dow AMP-95 and Grays AHY-95; The water-based leveling agent is a conventional water-based leveling agent, such as afcona 3590, BYK-333, Tech-2841; The water-based thixotropic agent is a conventional water-based accelerator, such as afcona 6530 and RHEOLATE HX-6008.

[0020] In the invention, the particle sizes of the fillers, such as heavy calcium, talcum powder and kaolin, reach 1000 meshes, and the particle size of the sericite powder reaches 800 meshes.

[0021] The color of the water-based acrylic polyurethane antistatic coating of the present invention can be adjusted as needed by adjusting the addition ratio of anatase titanium dioxide, red iron oxide, medium chrome yellow, carbon black or phthalocyanine blue pigments to adjust the color of the coating to meet the needs of users.

[0022] The present invention is further described below in conjunction with specific embodiments. Example 1

[0023] A water-based acrylic polyurethane antistatic coating, comprising component A and component B in a mass ratio of 10:1; the component A comprises the following raw materials: 15 kg of deionized water, 30 kg of water-based acrylic resin, 20 kg of modified conductive barium sulfate powder, 1.5 kg of wetting dispersant afcona 4560, 1.5 kg of water-based defoamer afcona 2503, 5 kg of anatase titanium dioxide, 5 kg of heavy calcium, 5 kg of talc and 1 kg of ethylene glycol butyl ether; the component B comprises the following raw materials: 5 kg of modified conductive polyurethane resin and 0.5 kg of propylene glycol diacetate; The modified conductive polyurethane resin is obtained according to the following steps: 874.8 g of ferric chloride and 4957 g of propylene glycol diacetate were mixed to obtain an iron salt solution with a mass concentration of 15%; Under stirring, 201 g of pyrrole monomer was added to 1072 g of waterborne polyurethane resin in 5 portions, the temperature was raised to 40° C. and stirred for 10 minutes, an iron salt solution was added thereto, and stirring was continued for 2 hours to obtain a modified conductive polyurethane resin; The waterborne polyurethane resin has a solid content of 60% and an NCO content of 14%; The modified conductive barium sulfate powder is obtained by coprecipitating barium sulfate powder with antimony salt and tin salt, and specifically comprises the following steps: 1.1 kg of antimony trichloride and 11.1 kg of tin dichloride dihydrate were added to 30.55 kg of 4 mol / L dilute hydrochloric acid, heated to 58° C. and stirred for 2 hours to obtain a precursor solution; 10 kg of barium sulfate powder was added to 111 kg of deionized water, and ultrasonically dispersed evenly. The mixture was heated to 73 ° C and stirred for 1 hour. The precursor solution was added dropwise at a rate of 0.2 L / min. After the addition was completed, the pH was adjusted to 1.0 with ammonia water, and the temperature was raised to 88 ° C and stirred for 18 hours. The mixture was filtered, washed with ethanol, dried, and calcined at 550 ° C for 2 hours to obtain modified conductive barium sulfate powder. Example 2

[0024] A water-based acrylic polyurethane antistatic coating, comprising component A and component B in a mass ratio of 20:1; the component A comprises the following raw materials: 25 kg of deionized water, 45 kg of water-based acrylic resin, 30 kg of modified conductive barium sulfate powder, 1 kg of wetting dispersant BYK-191, 1 kg of water-based defoamer afcona2502, 3 kg of water-based thixotropic agent afcona 6530, 15 kg of red iron oxide, 10 kg of talc, 10 kg of kaolin and 3 kg of ethylene glycol butyl ether; the component B comprises the following raw materials: 9 kg of modified conductive polyurethane resin and 2 kg of propylene glycol diacetate; The modified conductive polyurethane resin is obtained according to the following steps: 2127.8 g of iron salt and 8511 g of propylene glycol diacetate were mixed to obtain an iron salt solution with a mass concentration of 20%; Under stirring, 268 g of pyrrole monomer was added to 857.6 g of waterborne polyurethane resin in 6 portions, the temperature was raised to 50° C. and stirred for 10 minutes, an iron salt solution was added thereto, and stirring was continued for 1.5 hours to obtain a modified conductive polyurethane resin; The waterborne polyurethane resin has a solid content of 75% and an NCO content of 21%; The modified conductive barium sulfate powder is obtained by coprecipitating barium sulfate powder with antimony salt and tin salt, and specifically comprises the following steps: 1.78 kg of antimony trichloride and 15 kg of tin dichloride dihydrate were added to 42.85 kg of 6 mol / L dilute hydrochloric acid, heated to 62° C. and stirred for 3 hours to obtain a precursor solution; 15 kg of barium sulfate powder was added to 142.8 kg of deionized water, ultrasonically dispersed evenly, heated to 77 ° C and stirred for 2 hours, and the precursor solution was added dropwise at a rate of 0.5 L / min. After the addition was completed, the pH was adjusted to 2.0 with ammonia water, the temperature was raised to 92 ° C and stirred for 20 hours, filtered, washed with ethanol, dried, and calcined at 650 ° C for 3 hours to obtain modified conductive barium sulfate powder. Example 3

[0025] A water-based acrylic polyurethane antistatic coating, comprising component A and component B in a mass ratio of 12:1; the component A comprises the following raw materials: 18 kg of deionized water, 32 kg of water-based acrylic resin, 28 kg of modified conductive barium sulfate powder, 1 kg of water-based pH regulator Dow AMP-95, 1 kg of water-based defoamer afcona2502, 1.5 kg of water-based thixotropic agent RHEOLATE HX-6008, 6 kg of medium chrome yellow, 6 kg of kaolin, 6 kg of sericite powder and 1.5 kg of ethylene glycol butyl ether; the component B comprises the following raw materials: 6 kg of modified conductive polyurethane resin and 0.8 kg of propylene glycol diacetate; The solid content of water-based acrylic resin is 28%, and the hydroxyl content is 1.8%; The modified conductive polyurethane resin is obtained according to the following steps: 972 g of ferric chloride and 5103 g of propylene glycol diacetate were mixed to obtain an iron salt solution with a mass concentration of 16%; Under stirring, 201 g of pyrrole monomer was added to 804 g of waterborne polyurethane resin in four portions, the temperature was raised to 42° C. and stirred for 12 minutes, an iron salt solution was added thereto, and stirring was continued for 1.6 hours to obtain a modified conductive polyurethane resin; The waterborne polyurethane resin has a solid content of 65% and an NCO content of 15%; The modified conductive barium sulfate powder is obtained by coprecipitating barium sulfate powder with antimony salt and tin salt, and specifically comprises the following steps: 1.6 kg of antimony trichloride and 15.1 kg of tin dichloride dihydrate were added to 41.2 kg of dilute hydrochloric acid with a mass concentration of 5.5 mol / L, heated to 60° C. and stirred for 2.5 hours to obtain a precursor solution; 14 kg of barium sulfate powder was added to 147.3 kg of deionized water, ultrasonically dispersed evenly, heated to 74 ° C and stirred for 1.5 hours, and the precursor solution was added dropwise at a rate of 0.3 L / min. After the addition was completed, the pH was adjusted to 1.2 with ammonia water, the temperature was raised to 89 ° C and stirred for 19 hours, filtered, washed with ethanol, dried, and calcined at 580 ° C for 2.5 hours to obtain modified conductive barium sulfate powder. Example 4

[0026] A water-based acrylic polyurethane antistatic coating, comprising a component A and a component B in a mass ratio of 14:1; the component A comprises the following raw materials: 20 kg of deionized water, 35 kg of water-based acrylic resin, 28 kg of modified conductive barium sulfate powder, 2 kg of wetting dispersant Tech-8045, 1 kg of water-based defoamer Tech-321W, 1 kg of water-based leveling agent BYK-333, 8 kg of carbon black, 5 kg of heavy calcium, 5 kg of talc, 4 kg of kaolin and 2.5 kg of ethylene glycol butyl ether; the component B comprises the following raw materials: 8 kg of modified conductive polyurethane resin and 1.2 kg of propylene glycol diacetate; The solid content of water-based acrylic resin is 42% and the hydroxyl content is 3.3%; The modified conductive polyurethane resin is obtained according to the following steps: 1296 g of ferric chloride and 5904 g of propylene glycol diacetate were mixed to obtain an iron salt solution with a mass concentration of 18%; Under stirring, 268 g of pyrrole monomer was added to 974.5 g of waterborne polyurethane resin in 5 portions, the temperature was raised to 48° C. and stirred for 18 minutes, an iron salt solution was added thereto, and stirring was continued for 1.8 hours to obtain a modified conductive polyurethane resin; The waterborne polyurethane resin has a solid content of 70% and an NCO content of 15%; The modified conductive barium sulfate powder is obtained by coprecipitating barium sulfate powder with antimony salt and tin salt, and specifically comprises the following steps: 1.47 kg of antimony trichloride and 14.14 kg of tin dichloride dihydrate were added to 39.2 kg of dilute hydrochloric acid with a mass concentration of 4.5 mol / L, heated to 61° C. and stirred for 2.5 hours to obtain a precursor solution; 14 kg of barium sulfate powder was added to 140 kg of deionized water, ultrasonically dispersed evenly, heated to 75 ° C and stirred for 1.5 hours, and the precursor solution was added dropwise at a rate of 0.4 L / min. After the addition was completed, the pH was adjusted to 1.5 with ammonia water, the temperature was raised to 90 ° C and stirred for 19 hours, filtered, washed with ethanol, dried, and calcined at 600 ° C for 2.5 hours to obtain modified conductive barium sulfate powder. Example 5

[0027] A water-based acrylic polyurethane antistatic coating, comprising component A and component B in a mass ratio of 15:1; the component A comprises the following raw materials: 18 kg of deionized water, 35 kg of water-based acrylic resin, 22 kg of modified conductive barium sulfate powder, 1 kg of wetting dispersant Tech-8045, 2 kg of water-based defoaming agent afcona2502, 1 kg of water-based pH regulator Dow Grays AHY-95, 8 kg of phthalocyanine blue, 3 kg of talc, 6 kg of kaolin, 5 kg of sericite powder and 2 kg of ethylene glycol butyl ether; the component B comprises the following raw materials: 6 kg of modified conductive polyurethane resin and 1 kg of propylene glycol diacetate; The solid content of water-based acrylic resin is 35%, and the hydroxyl content is 2.5%; The modified conductive polyurethane resin is obtained according to the following steps: 967.2 g of ferric nitrate and 4406 g of propylene glycol diacetate were mixed to obtain an iron salt solution with a mass concentration of 18%; Under stirring, 134 g of pyrrole monomer was added to 536 g of waterborne polyurethane resin in 5 portions, the temperature was raised to 45° C. and stirred for 15 minutes, an iron salt solution was added thereto, and stirring was continued for 2 hours to obtain a modified conductive polyurethane resin; The waterborne polyurethane resin has a solid content of 70% and an NCO content of 20%; The modified conductive barium sulfate powder is obtained by coprecipitating barium sulfate powder with antimony salt and tin salt, and specifically comprises the following steps: 1.2 kg of antimony trichloride and 11.2 kg of tin dichloride dihydrate were added to 30.8 kg of 5 mol / L dilute hydrochloric acid, heated to 60° C. and stirred for 2.5 hours to obtain a precursor solution; 11 kg of barium sulfate powder was added to 110 kg of deionized water, ultrasonically dispersed evenly, heated to 75 ° C and stirred for 1.5 hours, and the precursor solution was added dropwise at a rate of 0.4 L / min. After the addition was completed, the pH was adjusted to 1.5 with ammonia water, the temperature was raised to 90 ° C and stirred for 19 hours, filtered, washed with ethanol, dried, and calcined at 600 ° C for 2.5 hours to obtain modified conductive barium sulfate powder. Example 6

[0028] The method for preparing the water-based acrylic polyurethane antistatic coating described in Example 1 comprises the following steps: ① Grind 5kg of anatase titanium dioxide, 5kg of heavy calcium carbonate, 5kg of talc, 15kg of deionized water and 1kg of ethylene glycol butyl ether to less than 40μm, filter, add 30kg of water-based acrylic resin, 20kg of modified conductive barium sulfate powder, 1.5kg of wetting dispersant afcona 4560, and 1.5kg of water-based defoaming agent afcona 2503, and stir evenly to obtain component A; ② Mix 5 kg of modified conductive polyurethane resin and 0.5 kg of propylene glycol diacetate and stir evenly to obtain component B; When in use, component A and component B are stirred and mixed at a mass ratio of 10:1 to obtain a water-based acrylic polyurethane antistatic coating. Example 7

[0029] The preparation method of the water-based acrylic polyurethane antistatic coating described in Example 2 comprises the following steps: ① Grind 15kg of red iron oxide, 10kg of talcum powder, 10kg of kaolin, 25kg of deionized water and 3kg of ethylene glycol butyl ether to less than 40μm, filter, add 45kg of water-based acrylic resin, 30kg of modified conductive barium sulfate powder, 1kg of wetting and dispersing agent BYK-191, 1kg of water-based defoaming agent afcona2502 and 3kg of water-based thixotropic agent afcona 6530, stir evenly to obtain component A; ② Mix 9 kg of modified conductive polyurethane resin and 2 kg of propylene glycol diacetate and stir evenly to obtain component B; When in use, component A and component B are stirred and mixed at a mass ratio of 20:1 to obtain a water-based acrylic polyurethane antistatic coating. Example 8

[0030] The method for preparing the water-based acrylic polyurethane antistatic coating described in Example 3 comprises the following steps: ① Grind 6kg of medium chrome yellow, 6kg of kaolin, 6kg of sericite powder, 18kg of deionized water and 1.5kg of ethylene glycol butyl ether to less than 40μm, filter, add 32kg of water-based acrylic resin, 28kg of modified conductive barium sulfate powder, 1kg of water-based pH regulator Dow AMP-95, 1kg of water-based defoamer afcona2502, and 1.5kg of water-based thixotropic agent RHEOLATE HX-6008, stir at 2800 rpm for 70 minutes, and mix to obtain component A; ② Mix 6 kg of modified conductive polyurethane resin and 0.8 kg of propylene glycol diacetate and stir evenly to obtain component B; When in use, component A and component B are stirred and mixed at a mass ratio of 12:1 to obtain a water-based acrylic polyurethane antistatic coating. Example 9

[0031] The method for preparing the water-based acrylic polyurethane antistatic coating described in Example 4 comprises the following steps: ① Grind 8kg of carbon black, 5kg of heavy calcium, 5kg of talc, 4kg of kaolin, 20kg of deionized water and 2.5kg of ethylene glycol butyl ether to less than 40μm, filter, add 35kg of water-based acrylic resin, 28kg of modified conductive barium sulfate powder, 2kg of wetting and dispersing agent Tech-8045, 1kg of water-based defoaming agent Tech-321W, and 1kg of water-based leveling agent BYK-333, stir at 4200 rpm for 40 minutes, and mix to obtain component A; ② Mix 8 kg of modified conductive polyurethane resin and 1.2 kg of propylene glycol diacetate and stir evenly to obtain component B; When in use, component A and component B are stirred and mixed at a mass ratio of 14:1 to obtain a water-based acrylic polyurethane antistatic coating. Example 10

[0032] The method for preparing the water-based acrylic polyurethane antistatic coating described in Example 5 comprises the following steps: ① Grind 8kg of phthalocyanine blue, 3kg of talc, 6kg of kaolin, 5kg of sericite powder, 18kg of deionized water and 2kg of ethylene glycol butyl ether to below 40μm, filter, add 35kg of water-based acrylic resin, 22kg of modified conductive barium sulfate powder, 1kg of wetting dispersant Tech-8045, 2kg of water-based defoaming agent AFCONA2502, and 1kg of water-based pH regulator Dow Gerris AHY-95, stir at 3000 rpm for 50 minutes, and mix to obtain component A; ② Mix 6 kg of modified conductive polyurethane resin and 1 kg of propylene glycol diacetate and stir evenly to obtain component B; When in use, component A and component B are stirred and mixed at a mass ratio of 15:1 to obtain a water-based acrylic polyurethane antistatic coating.

[0033] The performance of the water-based acrylic polyurethane antistatic coating obtained in Examples 6 to 10 was tested, and the results are shown in Table 1. The coating hardness was tested according to the method for measuring the hardness of the paint film by the pencil method of paint and varnish GB / T 6739-2022, the adhesion was tested according to the cross-cut test method of paint and varnish GB / T 9286-2021, the salt water resistance was tested according to the method for measuring the resistance of paint and varnish to liquid media GB / T 9274-1988, the salt spray resistance was tested according to the method for measuring the resistance of paint and varnish to neutral salt spray GB / T 1771-2007, the solvent resistance was tested according to the method for measuring the resistance of paint and varnish to chemical reagents GB / T 1763-1989, the water resistance was tested according to the method for measuring the water resistance of paint film GB / T 1733-1993, and the resistivity was tested according to the method for testing the electrical properties of wires and cables Part 5: Insulation resistance test method.

[0034] Table 1 Performance test results of waterborne acrylic polyurethane antistatic coatings obtained in Examples 6 to 10

[0035] It can be seen from the results in Table 1 that the waterborne acrylic polyurethane antistatic coating of the present invention can achieve a paint film adhesion of level 0 under environmental tests such as water resistance, salt water resistance, salt spray resistance and solvent resistance, and the surface resistivity is maintained at 10 5 Ω level, even 10 4 Ω level, has a good anti-static effect, and the coating has good hardness.

Claims

1. A water-based acrylic polyurethane antistatic coating, characterized in that: The composition comprises component A and component B in a mass ratio of 10-20:1; in parts by weight, the component A comprises the following raw materials: 15-25 parts of deionized water, 30-45 parts of waterborne acrylic resin, 20-30 parts of modified conductive barium sulfate powder, 3-5 parts of functional additives, 5-15 parts of pigments, 10-20 parts of fillers and 1-3 parts of ethylene glycol butyl ether; the component B comprises the following raw materials: 5-9 parts of modified conductive polyurethane resin and 0.5-2 parts of propylene glycol diacetate; The modified conductive polyurethane resin is obtained according to the following steps: The iron salt and propylene glycol diacetate are mixed uniformly to obtain an iron salt solution with a mass concentration of 15-20%; Under stirring, the pyrrole monomer is added to the waterborne polyurethane resin several times, the temperature is raised to 40-50° C. and stirred for 10-20 minutes, an iron salt solution is added thereto, and stirring is continued for 1.5-2 hours to obtain a modified conductive polyurethane resin; The mass ratio of pyrrole monomer to waterborne polyurethane resin is 15-25:80; The molar ratio of iron salt to pyrrole in the iron salt solution is 1.8-2.2:1; The waterborne polyurethane resin has a solid content of 60-75% and an NCO content of 14-21%; The modified conductive barium sulfate powder is obtained by coprecipitating barium sulfate powder with antimony salt and tin salt.

2. The water-based acrylic polyurethane antistatic coating according to claim 1, characterized in that: The modified conductive barium sulfate powder is prepared according to the following steps: Add antimony trichloride and tin dichloride dihydrate into dilute hydrochloric acid, heat to 58-62°C and stir for 2-3 hours to obtain a precursor solution; The barium sulfate powder is added to deionized water, ultrasonically dispersed uniformly, heated to 73-77°C and stirred for 1-2 hours, the precursor solution is added dropwise at a rate of 0.2-0.5 L / min, and after the addition is completed, the pH is adjusted to 1.0-2.0 with ammonia water, the temperature is raised to 88-92°C and stirred for reaction for 18-20 hours, filtered, washed with ethanol, dried, and calcined at 550-650°C for 2-3 hours to obtain modified conductive barium sulfate powder; The mass ratio of the antimony trichloride, tin dichloride dihydrate, dilute hydrochloric acid, barium sulfate powder and deionized water is 2-2.5:20-21:55-60:18-21:

200.

3. The water-based acrylic polyurethane antistatic coating according to claim 1, characterized in that: The functional additive is two or more of a wetting and dispersing agent, an aqueous defoaming agent, an aqueous pH regulator, an aqueous leveling agent, and an aqueous thixotropic agent.

4. The water-based acrylic polyurethane antistatic coating according to claim 1, characterized in that: The pigment is one or more of anatase titanium dioxide, red iron oxide, medium chrome yellow, carbon black or phthalocyanine blue.

5. The water-based acrylic polyurethane antistatic coating according to claim 1, characterized in that: The filler is two or more of heavy calcium, talcum powder, kaolin or sericite powder.

6. The water-based acrylic polyurethane antistatic coating according to claim 1, characterized in that: The solid content of water-based acrylic resin is 28~42%, and the hydroxyl content is 1.8~3.3%.

7. The water-based acrylic polyurethane antistatic coating according to claim 2, characterized in that: The mass concentration of the dilute hydrochloric acid is 4-6 mol / L.

8. The water-based acrylic polyurethane antistatic coating according to claim 1, characterized in that: The iron salt is ferric chloride or ferric nitrate.

9. The method for preparing a water-based acrylic polyurethane antistatic coating according to claim 1, characterized in that: The following steps are involved: ① Grind 5-15 parts of pigment, 10-20 parts of filler, 15-25 parts of deionized water and 1-3 parts of ethylene glycol butyl ether to less than 40 μm by weight, add 30-45 parts of water-based acrylic resin, 20-30 parts of modified conductive barium sulfate powder and 3-5 parts of functional additives after filtering, and stir evenly to obtain component A; ② Mix 5-9 parts of modified conductive polyurethane resin and 0.5-2 parts of propylene glycol diacetate and stir evenly to obtain component B; When in use, component A and component B are stirred and mixed at a mass ratio of 10-20:1 to obtain a water-based acrylic polyurethane antistatic coating.

10. The method for preparing a water-based acrylic polyurethane antistatic coating according to claim 9, characterized in that: In step ①, the stirring speed is 2800-4200 rpm, and the stirring time is 40-70 minutes.

Citation Information

Patent Citations

  • A compound conductive powder with BaSO4 and its making method

    CN101123126A

  • High elastic aqueous conductive nano coating

    CN101353547A

  • Preparation method for cationic aqueous polyurethane / polypyrrole conductive composite

    CN103013093A

  • Waterborne antistatic wear-resistant coating

    CN105038371A

  • Preparation method of polypyrrole / polyurethane composite conductive hydrogel

    CN109912816A